2017
DOI: 10.1080/10408398.2017.1322551
|View full text |Cite
|
Sign up to set email alerts
|

Famine exposure during early life and risk of hypertension in adulthood: A meta-analysis

Abstract: This meta-analysis confirmed the association between exposure to famine in early life and increased risk of hypertension in adulthood. Prevention of malnutrition during early life is an appropriate recommendation to prevent hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Famine periods can be seen as natural experiments that can provide unique insights into the influence of early‐life undernutrition on the development of cardiometabolic conditions during adulthood that go beyond early body size. The associations of famine in early life with overweight, obesity, hyperglycaemia, T2DM, hypertension, and metabolic syndrome have been summarized in several meta‐analyses of observational studies . In the first meta‐analysis on this topic, exposure to the Chinese famine in early life was associated with a higher risk of metabolic syndrome in adulthood but not with the other outcomes mentioned above, possibly because of the limited number of studies included in each analysis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Famine periods can be seen as natural experiments that can provide unique insights into the influence of early‐life undernutrition on the development of cardiometabolic conditions during adulthood that go beyond early body size. The associations of famine in early life with overweight, obesity, hyperglycaemia, T2DM, hypertension, and metabolic syndrome have been summarized in several meta‐analyses of observational studies . In the first meta‐analysis on this topic, exposure to the Chinese famine in early life was associated with a higher risk of metabolic syndrome in adulthood but not with the other outcomes mentioned above, possibly because of the limited number of studies included in each analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the first meta‐analysis on this topic, exposure to the Chinese famine in early life was associated with a higher risk of metabolic syndrome in adulthood but not with the other outcomes mentioned above, possibly because of the limited number of studies included in each analysis. Some of the outcomes investigated in the first meta‐analysis, including overweight, obesity, T2DM, and hypertension, were updated later in several meta‐analyses that included several non‐Chinese studies. While the updated results showed that early life exposure to famine was associated with increased risks of overweight, obesity, T2DM, and hypertension in adulthood, many aspects of these associations remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on animal and human studies, low birth-weight babies and nutrient de ciency were likely to have endothelial dysfunction, less vascular elastin, increased sympathetic tone and liver-derived dyslipidemias [32,33].In addition, increased sympathetic tone was commonly associated with hypertension in animal models of both under nutritional and over nutritional states [34]. It was now generally accepted that exposure to famine in early life was closely related to adult hypertension [35], and that hypertension was an independent risk factor for AAD [36]. The mechanism of AAD is unclear.…”
Section: Discussionmentioning
confidence: 99%